THE MYSTERY OF TRINITY: The Relevance and Importance of the Most Holy Trinity in the Christian Arena based on the Writings of Hans Urs von Balthasar - Athappilly, Sebastian (Journal of Dharma, 2020)
Devasiachan Mukulathu. The Mystery of Trinity. The Relevance and Importance of the Most Holy Trinity in the Christian Arena based on the Writings of Hans Urs von Balthasar. Bengaluru: Dharmaram Publications (No 434), 2019, pp. xviii + 356.